DARI VERBA LEKSIKAL MENJADI VERBA PENGHUBUNG: SEKILAS IKHWAL ALTERNASI VERBA DALAM BAHASA INGGRIS - Ikmi Nur Oktavianti (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Verb is considered as the central element in a linguistic construction, including in English. Chafe (1970:96) stated that verb determines the arguments. It is the semantic aspect of the verb that selects the arguments in the construction. However, a single verb can possibly have different semantic aspect in different condition. It will, then, influence the valence of the verb and definitely the argument of the verb. This change is so-called alternation. This also happens in English. One of the examples is the change of lexical verb into linking verb. Therefore, this paper attempts to describe the semantic change of lexical verb into linking verb.